National u16, u18 and u20 reserve basketball teams: special physical fitness analysis - Averyasova, Y. O.; Filimonova, S. I.; Shutova, T. N.; Andryushchenko, O. N. (Theory and Practice of Physical Culture, 2019)
National basketball teams of Russia have lately shown notable regresses on the global arenas, and the situation needs to be responded by special efforts to analyze the problems of the national basketball and reasons for the failures and take urgent actions based on a sound theoretical and practical basis to improve the basketball elite training systems. The study analyzes the special physical fitness test data of the men`s and women`s national U16, U18 and U20 reserve basketball teams. The study was timed to the 2018 precompetitive training periods prior to the top-ranking international tournaments. The women`s group physical fitness tests found the U18 and U20 group fitness being actually no better than the U16 one in every test. The men`s groups were also tested with no physical fitness progress in the U20 versus U16 and U18. It should be also mentioned that every age group showed too high mean square deviations in the tests, particularly in the 3-point scores and HR recovery rates after the speed endurance tests. The test data showed the training systems being in need of revisions to secure progress. The authors recommend that special attention should be given to prospects selection for the precompetitive trainings based on the performance test data produced by the cutting-edge test systems; with a due priority to the psychological and coaching service in the individualized and group trainings customized to the players` ages, body types and other individual specifics.